CallDetect: Detection of Call Log Exploitation Inspired by Apoptosis - Madihah Mohd Saudi; Azuan Ahmad; Amirul Adli Che Ismail; Muhammad ‘Afif Husainiamer (Indonesian Society for Knowledge and Human Development, 2024)
Indexed by SCOPUS/ERA